Pemasangan Dua Merek Implan pada Satu Pasien - Santoso, Alice; Ariesanti, Yessy (Jurnal Kedokteran Gigi Terpadu, 2024)
Introduction: Dental implants have been used in dentistry for more than half a century and have a high success rate (90 - 95%). The number of implant patients has increased today and is expected to continue to increase for the next few years. Various studies have been conducted to find the best implant material. Titanium and its mixtures are still the material of choice for implants today. The author wants to present a case report of a 39-year-old man who underwent the installation of two implants in the mandibular region Case Report: A 39-year-old man came in with a complaint of missing right and lower left back teeth since 7 years ago due to caries. The patient has a smoking habit. The patient is planned to undergo the implantation of 37 teeth with biotec BTK and 47 teeth with Straumann. The implant was well installed and no complications were found. Patients are asked to keep the implant area and oral cavity clean, as well as routinely check with the dentist every 6 months. Discussion: Biotec implants (BTK) are implants made of pure titanium (Ti) grade 4 (ASTM F 67 / ISO 2832-2) while Straumann implants are made of Roxolid (85% titanium and 15% Zirconia [TiZr]). Conclusion:  Titanium Zirconium (TiZr) and pure Titanium are the preferred materials in the field of implants. Both can be well integrated and are able to restore optimal chewing function.